化简(a+2)(a-2)+3(a+2)²-6a(a+2)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/05 23:21:07
化简(a+2)(a-2)+3(a+2)²-6a(a+2)化简(a+2)(a-2)+3(a+2)²-6a(a+2)化简(a+2)(a-2)+3(a+2)²-6a(a+2)=
化简(a+2)(a-2)+3(a+2)²-6a(a+2)
化简(a+2)(a-2)+3(a+2)²-6a(a+2)
化简(a+2)(a-2)+3(a+2)²-6a(a+2)
=(a+2)×[(a-2)+3(a+2)-6a]
=(a+2)×[a-2+3a+6-6a]
=(a+2)(4-2a)
=-2(a+2)(a-2)
=-2(a²-4)
=-2a²+8
原式=(a+2)[(a-2)+3(a+2)-6a]
=(a+2)(a-2+3a+6-6a)
=(a+2)(-2a+4)
=-2(a+2)(a-2)
=-2(a²-4)
=-2a²+8
提出一个(a 2)为
(a 2)(a-2 3a 6-6a)
=(a 2)(-2a 4)
=(a 2)(a-2)×(-2)
=-2×(a²-2²)
=-2a² 8
不懂可追问,望采纳
(a+2)(a-2)+3(a+2)(a+2)-6a(a+2)
(a+2)(a-2+3a+6-6a)
(a+2)(4-2a)
答案:2(a+2)(2-a)
化简; a-2a+3a-4a+5a-6a+``````-2006a+2007a.
化简:a-2a+3a-4a+5a-6a+.+2010a+2011a.
[a/(a-1)+a/(a+2)](a+2)/(2a平方+3a+1)化简
化简:[2/3a - 2/(a+b) * (a+b/3a - a - b)] / (a-b)/a
化简(a/a-2-a/a+3)*a^2+a-6/a
化简(a/a-2-a/a+2)×4-a/a(a/a-2-a/a+2)×4-a/a
计算(3a×a)+(2a×3a)+(3a×a)+[a×(a+2a+2a+2a+a)]
(a 1)(a 2)(a 3)(a
(a+2)(a+1)-a(a-3)
化简(a+1)(a-2)/(a+2)(a-2)+3
化简10+3a-a^2/2+a-a^2
化简 3a-[5a-(a+2)+a]-1
|a-2|-|3-a|化简
化简(2a-a*a)(a*a+4a+3)/(a*a*a+a*a)(a*a+a-6),并求当4a+3/a=0时,此分式的值
化简a+2a-3a-4q+5a+6a-7a-8a+...2001a+2002a-2003a-2004a
化简 a-2a+3a-4a+5a'''''''+99a-100a a=-2 的值
化简:a(a*a-1)+2a*a(a+1)-3a(2a-5)拜托了各位
2a+a²/a-a 化简.(2a+a²/a)-a